The Effectiveness of Using the Telegram Application in Learning the Malay Culture Course at Universitas Riau - Hasnah Faizah; Eka Rahayu Putri; Muhammad Imam Arifandy; Nabilatuzzahwa Nabilatuzzahwa; Riski Alfalah (International Journal of Studies in International Education, 2025)
This study aims to analyze the effectiveness of using the Telegram application as an innovative digital learning medium in the Malay Culture course at Universitas Riau. The integration of technology in education has become essential in enhancing learning outcomes and student engagement, particularly in cultural-based subjects that require active interaction and collaboration. This research employed a qualitative descriptive method, with data collected through questionnaires, interviews, and documentation. The results indicate that the Telegram application provides significant benefits in facilitating the learning process. It enables efficient distribution of learning materials, smooth communication between lecturers and students, and the creation of interactive discussion spaces. Moreover, Telegram’s features—such as group chats, file sharing, and polls—encourage student participation, improve accessibility to resources, and foster collaborative learning. The study also found that students felt more motivated, independent, and responsible in managing their learning activities through this platform. Overall, the use of Telegram has proven to be effective, practical, and adaptable in supporting the teaching and learning process of the Malay Culture course. Therefore, it is recommended that Telegram be utilized not only in cultural studies but also across other academic disciplines to enhance the quality of online and blended learning environments.